DAMPAK PANDEMI COVID-19 TERHADAP PENGELUARAN PANGAN RUMAH TANGGA MISKIN PERKOTAAN: STUDI KASUS KELUARAHAN CIROYOM, KECAMATAN ANDIR, KOTA BANDUNG - Elvira Aulia Hasanah; Mahra Arari Heryanto; Hepi Hapsari; Trisna Insan Noor (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2021)
The impact of the pandemic has reduced the amount of food consumption expenditure for poor families due to declining incomes and delays in government social protection. Poor families are threatened with food insecurity, because their access to food becomes limited when cash availability decreases. This study aims to analyze the causes and factors of poor families becoming more food insecure and to find out how poor families manage their food expenditure during the Covid-19 pandemic. The research design was carried out using a system thinking approach. The analysis of the system uses content analysis based on the system archetype. The validation stage of the system structure uses triangulation techniques based on data collection and the PRA approach through the trend change chart technique. The results show that food insecurity for poor families occurs due to the impact of the pandemic which causes access to food for poor families to be increasingly limited, which is characterized by decreased food consumption in terms of quantity and quality. The main factor that influences it is the level of income. The strategy to maintain their family's food consumption needs is to apply for a loan and switch to cheap food sources so that food quality does not decrease as much as the food consumption budget.